PENGARUH KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN BAGIAN ZC. ASSEMBLING PT. XYZ - Yasnimar Ilyas; Kiki Amelia (Universitas Nusa Cendana, 2021)
XYZ is a company that produces apparel accessories that has been established for more than 30 years. However, there is a problem in decreasing of employee performance that can be seen on the attendance data of the employees. So, it is necessary to conduct a research to see what factors cause a decrease in employee performance. The purpose of this research is to see the relationship and influence between Competence and Work Environment on the Employee Performance. The method in this research is multiple linear regression. The results of data analysis in this study show that Competence has a significant influence on Employee Performance. The Work Environment does not have a significant effect on employee performance. Competence and Work Environment simultaneously have a significant effect on Employee Performance. In the determinant coefficient test (R²), the influence of Competence and Work Environment on Employee Performance is quite high as many as 0.555 or 55.5%. This means that Competence and Work Environment have a contribution of 55.5% to explain the Employee Performance, while 44.5% of other variables are not discussed in this study. Based on the regression test, the variable that most affected Employee Performance was the Competency variable (X1) with a value of 0.486 (positive value). Keywords: Competence, Work Environment, Employee Performance